(untitled)
Let R be a commutative Noetherian ring, I and J be two ideals of R, and M be an R-module. We study the cofiniteness and finiteness of the local cohomology module H^i_I,J (M) and give some conditions for the finiteness of Hom_R(R/I, H^s_ I,J (M)) and Ext^1_R(R/I, H^s_I,J (M)). Also, we get some results on the attached primes of H^dimM